TI_GERICHTE 52.2019.372 vom 5. Juni 2019 , Iscrizione nel catalogo elettorale di un Comune - determinazione del domicilio - TI Tribunale d'appello (2019)
Iscrizione nel catalogo elettorale di un Comune - determinazione del domicilio